2021
DOI: 10.1002/ajmg.a.62484
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects and copy number variants associated with neurodevelopmental impairment

Abstract: A genetic etiology is identifiable in 20%–30% of patients with congenital heart defects (CHD). Chromosomal microarray analysis (CMA) can detect copy number variants (CNV) associated with CHD. In previous studies, the diagnostic yield of postnatal CMA testing ranged from 4% to 28% in CHD patients. However, incidental pathogenic CNV and variants of unknown significance are often discovered without any known association with CHD. The study objective was to describe the rate of pathogenic CNV associated with neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
5
0
1
Order By: Relevance
“…[11] Some epidemiological studies have reported that children with CHD show more obvious neurodevelopmental disorders than children with normal cardiovascular development, and children with CHD may have a higher risk of social interaction and communication disorders. [12,13] This is similar to the characteristics of children with autism spectrum disorder (ASD).…”
Section: Introductionmentioning
confidence: 62%
“…[11] Some epidemiological studies have reported that children with CHD show more obvious neurodevelopmental disorders than children with normal cardiovascular development, and children with CHD may have a higher risk of social interaction and communication disorders. [12,13] This is similar to the characteristics of children with autism spectrum disorder (ASD).…”
Section: Introductionmentioning
confidence: 62%
“…A total of 170 articles were included in the final review (alphabetically ordered based on author in Supplementary Table 2). 1,2,7–50,55,56,68–189 A PRISMA flow diagram is presented to track the process and number of studies included and excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A further 74 articles were secondarily excluded from the quantitative analysis. Of these, 38 did not provide quantitative data [ 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], in 22 articles it was not possible to infer a quantitative analysis of incremental yield of CMA over standard karyotyping [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 …”
Section: Resultsmentioning
confidence: 99%